Expanding the Donor Pool Through Intensive Care to Facilitate Organ Donation: Results of a Spanish Multicenter Study. Issue 8 (August 2017) - Domínguez-Gil, Beatriz; Coll, Elisabeth; Elizalde, José; Herrero, Jaime E.; Pont, Teresa; Quindós, Brígida; Marcelo, Bella; Bodí, María A.; Martínez, Adolfo; Nebra, Agustín; Guerrero, Francisco; Manciño, José M.; et al.
Abstract : Background: Intensive Care to facilitate Organ Donation (ICOD) may help to increase the donor pool. We describe the Spanish experience with ICOD. Methods: Achieving Comprehensive Coordination in Organ Donation (ACCORD)-Spain consisted of an audit of the donation pathway from patients who died as a result of a devastating brain injury (possible donors) in 68 hospitals during November 1, 2014, to April 30, 2015. We focused on possible donors whose families were interviewed to discuss organ donation once intensive care with a therapeutic purpose was deemed futile and brain death (BD) was a likely outcome. Results: Of the 1970 possible donors in ACCORD-Spain, in 257, the family was interviewed once the decision had been made not to intubate/ventilate (n = 105), with the patient under intubation/ventilation outside of the intensive care unit (n = 59), or with the patient intubated/ventilated within the intensive care unit (n = 93). Consent to ICOD was obtained in 174 cases. Consent was higher when the donor coordinator participated in the interview (odds ratio, 2.32; 95% confidence interval, 1.33-4.11; P = 0.003). One hundred thirty-one patients developed BD, of whom 117 transitioned to actual donation after BD. Of the 35 patients who did not develop BD, 2 transitioned to actual donation after circulatory death. Sixteen patients subject to ICOD were finally medically unsuitable organ donors. ICOD contributed to 24% of the 491 actual donors registered in ACCORD-Spain. Conclusions: Despite the complexity of the interview, the majority of families consented to ICOD. Estimating the probability of BD and assessing medical suitability are additional challenges of the practice. ICOD represents a clear opportunity to increase the donor pool and ensures organ donation is posed at every end-of-life care pathway. Abstract : This article describes the complexities, challenges and performance of the use of intensive care to facilitate organ donation in Spain, an approach still underexplored to increase the donor pool.